Hydrogenation of CO2 catalyzed by thermally decomposed cobalt-containing alkaline earth metal carbonates - Gupta, Sharad; Vinod, C. P.; Poupin, Christophe; Jagadeesan, Dinesh (Energy & Fuels, 2025)
CO2 hydrogenation over Co catalysts supported on alkaline earth metal oxides was investigated. The catalysts were prepared by thermally decomposing alkaline metal carbonates CoMCO3, where M = Mg, Ca, Sr, and Ba, in H2. During the thermal activation, contingent upon the thermal stability of the precursor, it transformed into a composite of metal oxides, metals, and undecomposed metal carbonates. The thermal activation temperature, the ratio of CO2 to H2, the composition, and the basicity of the catalyst all played a significant role in influencing the conversion of CO2 and the selectivity to CH4. Among the various Co-containing alkaline earth metal carbonate precursors, CoCaCO3 activated at 400 degrees C yielded the highest steady-state CO2 conversion of 54% with a CH4 selectivity of 89.8% throughout 28 h in the reaction stream containing a 1:4 ratio of CO2 and H2. Detailed characterization showed that the CaCo-400 catalyst contained metallic Co, CaO, and undecomposed CaCO3 phases. The study assumes significance in understanding the role of the composition of catalysts in the formation of CO2 hydrogenation.